Making Use of Patient-Reported Outcome Measures for Haemorrhoidal Disease in Clinical Practice: A Perspective - Kuiper, Sara Z.; Kimman, Merel L.; Rørvik, Håvard D.; Olaison, Gunnar; Breukink, Stephanie O. (Frontiers in Surgery, 2021)
Haemorrhoidal disease (HD) affects millions of people around the world and for most it is a recurring problem. Increasingly, clinicians broaden their focus on the patient’s experiences with haemorrhoidal symptoms, including their impact on daily life. The patient’s experience can be assessed using a patient-reported outcome measure (PROM). A PROM facilitates a deeper understanding of the disease-burden and allows a clinician to obtain information directly from the patients about their experiences with the ailment. Over the last years, PROMs have shown their additional role to traditional outcomes for several diseases and have earned their place in the daily consultation room. In order to improve and personalize the treatment of HD, we endorse the use of validated PROMs in clinical care.